Characteristics of Co3O4 and cobalt nanostructured microspheres: Morphology, structure, reduction process, and magnetic properties. (March 2018) - Shatrova, Nadezda; Yudin, Andrey; Levina, Vera; Kuznetsov, Denis; Novakova, Alla; Dzidziguri, Ella; Perov, Nikolay; Issi, Jean-Paul
Graphical abstract: Highlights: The metal cobalt samples consist in both α-Со with a hexagonal close-packed lattice and β-Со face-centered cubic crystal at reduction temperatures 220, 240, 300 and 350 °C. Co3 O4 reduction proceeded in successive stages: water removal, residual salt removal, Co3 O4 → CoO and CoO → Co transitions. Inheritance of morphology may have droplet–Co3 O4 –Co association. Abstract: Nanostructured magnetic cobalt microspheres were synthesized using a two-stage method. First, nanostructured cobalt oxide Co3 O4 microspheres were produced by ultrasonic spray pyrolysis at different temperatures from 800 to 1100C. Second, the nanostructured powders obtained were reduced to metal cobalt in an hydrogen atmosphere at different temperatures from 220 to 350C. In this study the evolution of the morphology from Co3 O4 nanostructured microspheres to nanostructured Co, resulting from the Co3 O4 reduction process, and the structure of metal cobalt, were investigated. It was found that the metal cobalt agglomerates have the same shape and mean diameter (∼ 1, 5 μm) as those of the cobalt oxide, Co3 O4 . The amount of Co microspheres with smaller diameters decreased with increasing reduction temperature. Also, the β-Co content increased with increasing reduction temperature.